Personal and Professional Well-Being of Kindergarten Teachers - A Systematic Literature Review - Dafna Armoza-Levi; Alina S. Rusu (Babes-Bolyai University, 2023)
Research has shown that early childhood education can have a positive impact on individual career development and can reduce social problems, emphasizing the importance of investing in quality education for young children. Kindergarten teachers play a critical role in building a high-quality education. To achieve that, kindergarten teachers perform an increasing diversity of tasks, which can significantly affect their motivation to teach and their professional and personal well-being. Despite the assumed importance of the personal and professional well-being of kindergarten teachers, previous studies have focused on the school atmosphere and their mental health. The objective of this study is to evaluate the current state of research-informed knowledge regarding the well-being of kindergarten teachers. The methodological approach consists of a systematic literature review of the well-being dimensions of kindergarten teachers that can be found in the literature and the instruments that are most frequently used to assess the identified dimensions. The findings of this systematic review can have significant value in designing intervention programs aiming to foster the personal and professional well-being of kindergarten teachers.